Accounting for South/Non-South Real Wage Differentials and for Changes in Those Differentials over Time - Farber, Stephen C.; Newman, Robert J. (The Review of Economics and Statistics, 1987)
Stephen C. Farber, Robert J. Newman, Accounting for South/Non-South Real Wage Differentials and for Changes in Those Differentials over Time, The Review of Economics and Statistics, Vol. 69, No. 2 (May, 1987), pp. 215-223